Welsh Government Flying Start Programme Evaluation Using Linked Data - Lowe, Sarah; McGuinn, Laura; Quintela, Marcos; Player, Luke (International Journal of Population Data Science, 2018)
Introduction Flying Start (FS) is the Welsh Government’s (WG) flagship Early Years programme for families with children aged less than 4 years of age. Running since 2006, the four entitlements are: Free part-time childcare for 2-3 year olds Enhanced Health Visiting Parenting support Speech, language, and communication support Objectives and Approach Currently, while we know which areas in Wales are receiving FS support, individual-level data on which child received what entitlements is not available. This means that area-level outcomes can be used as proxy indicators but the individual impact of receiving FS support cannot be examined. This project describes the issues around collecting individual-level data in deprived Welsh regions, a pilot project to facilitate this collection and will report some emerging findings from the analysis of pilot data. Results Following from previous studies funded by the ESRC and WG (e.g. Supporting People Data Linking Feasibility Study), a Dataflow Development Project (DDP) has been launched to install Secure Anonymised Information Linkage (SAIL) appliances into 6 pilot Local Authorities in Wales. The SAIL appliance technology will provide Local Authorities with the ability to link individual-level data within a Local Authority or between Local Authorities and to securely anonymise data into the SAIL Databank or ADRC-W. The DDP will test acquiring the individual level FS data from pilot Local Authorities into SAIL. The project aims to evaluate FS by linking the FS cohort to a range of outcomes including health, education and social care. We will report emerging findings from the analysis of pilot data. Conclusion/Implications There is grow interest in using linked administrative data to evaluate government initiatives, and mounting enthusiasm in Local Government. If successful, this model is likely to be adopted by related WG programmes; improving the evidence base, facilitating effective evaluation, and adding to the data available for re-use in Wales.